Twisted Multi-Cosine Gaussian Schell-Model Arrays and Their Statistical Characteristics - Miaomiao Tang; Shijie Dong; Pengju Yuan; Yunzhe Yang; Yujie Zhou; Xinzhong Li (Photonics)
A novel class of random sources with a twisted multi-cosine Gaussian Schell model correlation function is introduced, termed the TMCGSM array. The spectral density and spectral degree of coherence of the TMCGSM array field upon propagation are investigated thoroughly. Numerical examples illustrate that such beams are capable of producing a non-uniform lattice profile in the far zone and exhibits an unusual rotation behavior. It is revealed that the twist factor can not only induce the array to rotate as a whole, but also has a modulation effect on the intensity of element lobes in the central area. We also demonstrated that an obvious twist effect could be observed in the coherence curves under certain conditions.